SOSIALISASI DAN APLIKASI TEKNOLOGI PEMUPUKAN BERIMBANG SPESIFIK LOKASI UNTUK MENINGKATKAN MUTU DAN HASIL TANAMAN KAKAO DI KECAMATAN SELEMADEG TABANAN - Sup adma, A.A. N.,; I N. Dibia; I G.N. Bagus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
Cacao plant at Subak Abian Buana Sari Dusun Megati Kelod, Desa Megati, Kecamatan Selemadeg Timur, Tabanan regency were relativelly new. The farmers did not understand cultivation and the exact fertilizer dosage for cacao plant in their locations.In this activity, the community servisce teams transferred to the farmers some informations about soil fertility, balance fertilization dosage, spesific locations fertilization dosage for cacao plant, and demonstration plots balance fertilization specific location for cacao plant at Subak Abian Buana Sari. The activity results that the farmers became to understand about soil fertility, balance fertilization, spesific location fertilization dosage for cacao plant and to observe demonstration plot balance fertilization for growth, development, and yields of cacao plant. The yields of cacao plant increased 88,89 % respectively compared to without demonstration plot. We hope the farmers at Subak Abian Buana Sari were able to treat them according to the given instructions.